1985
DOI: 10.2136/sssaj1985.03615995004900040043x
|View full text |Cite
|
Sign up to set email alerts
|

Crop‐Water Production Function Model for Saline Irrigation Waters

Abstract: The relationship between crop yield and seasonal amount of applied water (crop‐water production function) is required to determine optimum irrigation management. A model is developed for the computation of crop‐water production functions with saline irrigation waters. The model combines three relationships: yield and evapotranspiration, yield and average root zone salinity, and average root zone salinity and leaching fraction. The model allows plant growth adjustment, and therefore evapotranspiration adjustmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
90
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(97 citation statements)
references
References 0 publications
3
90
0
4
Order By: Relevance
“…Vários pesquisadores têm tentado desenvolver uma função de produção para as culturas em relação à água de irrigação salina (Letey et al, 1985;Letey & Dinar, 1986;Bresler, 1987). Esses modelos combinam relações entre rendimentos e evapotranspiração, entre rendimento e salinidade na zona radicular e entre salinidade na zona radicular e a fração de lixiviação.…”
Section: Introductionunclassified
“…Vários pesquisadores têm tentado desenvolver uma função de produção para as culturas em relação à água de irrigação salina (Letey et al, 1985;Letey & Dinar, 1986;Bresler, 1987). Esses modelos combinam relações entre rendimentos e evapotranspiração, entre rendimento e salinidade na zona radicular e entre salinidade na zona radicular e a fração de lixiviação.…”
Section: Introductionunclassified
“…It was reported that increased evaporation from the soil surface can counteract the reductions in K c caused by high EC e of the root zone (FAO, 1998). Letey et al (1985) and Shalhevet (1994) reported that the effects of soil salinity and water stress were interactive to crop evapotranspiration.…”
Section: Fig 7 Plant Water Deficit As Affected By Growth Conditionsmentioning
confidence: 99%
“…Because of this, under saline conditions, the K s reducing factor should only be applied with the dual K c approach (FAO, 1998). In reviewed articles on impacts of salinity on crop production, Letey et al (1985) and Shalhevet (1994) concluded that the effect of soil salinity and water stress are generally additive in their impacts on crop evapotranspiration. Therefore, the same yield-ET functions may hold for both water shortage induced stress and for salinity induced stress.…”
Section: Fig 7 Plant Water Deficit As Affected By Growth Conditionsmentioning
confidence: 99%
“…model for soil salinization as a function of amount and salinity of the irrigation water [Letey et al, 1985],…”
mentioning
confidence: 99%
“…Assumptions and limitations of the model were discussed by Letey et al [1985]. A disadvantage of the model is that it requires an iterative solution, because of the mutual dependence of RY, YD, LF, EC e , and DP.…”
mentioning
confidence: 99%